Demographic and Clinical Study on Patients Referred to The National Cancer Research Center for Pap Smears - Alabbody, Huda Hameed (Iraqi Journal of Science, 2018)
A pap test is a simple technique which can detect pre-cancerous and cancerous cells in the vagina and cervix. Cervical cancer is the easiest gynecologic cancer we could prevent it, with regular screening tests and follow-up this screening may avoid cervical cancer or detact it early.This study aims to estimate cytological changes and precancerus lesions during Pap smear test and visual inspection of the cervix on Iraqi women and determine the relationship with demographic characteristics. The study included 50 women aged 18-56 years (mean 39 ±10) in National Cancer of Research Center (NCRC) belong to Baghdad University. These women suffered from genital problems or for checking reproductive health status during the period from 1stDecember 2016 to 31stApril 2018 to perform the grossly inspection of the cervix and take papanacola smear. The results showed that 98% of the women were sexually active, 88% of them in premenapusal period and only (12%) in postmenapusal. Visual inspection of the cervix showed there were (40%) erosion lesions, cytology examination showed (90%) of non specific inflamation, 60% of reactive squamous metaplasia, 26% Koilocytotic atypia, 16% CIN1 or LGSIL. Women how used the contraception 68% and the most of them used pills. The women who had multiple births 26% , 18% had one, and 56 % were nulliparous . The causes of the visit were variable as for rotine checking 48% or to know the reason of abnormal vaginal discharge 22%. 46% of them were doing this test while 54% of them didn't make it previously. Therefore, we recommend by firm awareness and must perform pap smear screening for sexually active women to prevent precancereus lesions in the cervix and then avoid cervical cancer.